PERBANDINGAN PENGENAAN PBB SEKTOR PERDESAAN &PERKOTAAN DI PROVINSI DKI JAKARTA , BEKASI, & DEPOK BERDASARKAN SPPT PBB TAHUN 2014 & 2015 - Arianty, Fitria; Purwanto, Thesa Adi (Jurnal Vokasi Indonesia, 2015)
Tax on Land and Building, Rural and Urban Sector based on the regional regulation may vary from one region to another. This is because the imposition authority of tax on land and building, rural and urban sectors were handed over to local governments. This study aimed to compare the land and building, Rural and Urban Sector tax policies in DKI Jakarta, Bekasi, Depok, based on SPPT 2014 and 2015. In analyzing the problems of the imposition tax on land and building, rural and urban sectors in DKI Jakarta, Bekasi, Depok, information obtained from interviews with tax authorities and field observations. The land and building, Rural and Urban Sector tax policies in DKI Jakarta, Bekasi, Depok different in terms of tax rates, determination the amount of NJOPTKP, as well as the amount of NJOP. The amount of NJOP in Jakarta is higher and more diverse than the amount of NJOP in Depok and Bekasi. Determination the amount of NJOP in Jakarta also set more frequently, which every year than in the city of Depok and Bekasi. This is because the value of land and buildings in Jakarta faster rise than in Depok and Bekasi.